Universal Approach to Integrating Reduced Graphene Oxide into Polymer Electronics; Polymers; Vol. 15, iss. 24 - Abyzova E. G. Elena Gennadievna; Petrov I. S. Iljya Sergeevich; Bril I. I. Iljya Igorevich; Cheshev D. L. Dmitry Leonidovich; Ivanov A. A. Aleksey Alekseevich; Khomenko M. Maxim; Averkiev A. A. Andrey Alekseevich; Fatkullin M. I. Maksim Ilgizovich; Kogolev D. A. Dmitry Anatoljevich; Bolbasov E. N. Evgeny Nikolaevich; Matkovich A.; Chen Dzhin Dzhu; et al. (2023, 2023)
Title screen